Effect of direct current on hydrogen permeation behavior of X80 pipeline steel in Shanghai soil solution - Dong, Liang; Qiu, Yan; Song, Qinfeng; Gu, Yuhui (Engineering failure analysis, 2023)
•The C0 of the square wave is higher than that of the triangular wave, but less than the constant potential.•The square wave causes greater fluctuations of hydrogen atoms in the sample than the triangular wave.•The fluctuation of hydrogen atom concentration near the surface of the sample is greater than that inside.•The sample cycles between the formation and rupture of the corrosion product film, resulting in pitting corrosion. Dynamic direct current may cause hydrogen damage and corrosion in buried pipelines. In this study, the hydrogen permeation behavior of X80 steel in a simulated solution of Shanghai soil under dynamic DC interference was investigated using electrochemical hydrogen permeation testing and surface pH detection, combined with surface morphological observation and numerical simulation methods. The results show that the dynamic direct current causes alternating reduction (hydrogen precipitation) and oxidation reactions on the surface of the specimen and affects hydrogen permeation. At the same amplitude, the diffusible hydrogen concentration of square wave hydrogen permeation is greater than that of triangular wave. With the negative shift of the wave peak potential, the diffusible hydrogen concentration increases for both square and triangular wave hydrogen permeation. The specimens cycle between the generation and rupture of corrosion product films and cause pitting, which may increase the risk of localized hydrogen damage.